PERANAN BRANDING PROMOTION WONDERFUL INDONESIA PADA ASEAN TOURISM FORUM (ATF) DALAM MENIGKATKAN PARIWISATA DI INDONESIA - Taufiq Rahmat; Gunawan Undang (Program Studi Manajemen, Universitas Al Ghifari, 2021)
AbstractThis study aims to determine the role of the Wonderful Indonesia branding promotion at the Asean Tourism Forum (ATF) in improving tourism in Indonesia. The ASEAN Tourism Forum (ATF) is regional cooperation that seeks to promote the ASEAN region as an international tourist destination.The research method used is a qualitative method through literature reviews on official government documents, scientific articles, and news.The results show that the ASEAN Tourism Forum (ATF) is a means or media for Indonesia to attract foreign investors to invest or invest in cooperation in developing tourism in Indonesia, as well as the Wonderful Indonesia branding promotion media to attract foreign tourists to tourist destinations in Indonesia. Indonesia. The Indonesian government takes advantage of ATF activities, namely the ASEAN Tourism Marketing Strategic (ATMS), TRAVEX, and the ATF award for the best destinations in ASEAN to boost the prestige of Indonesian tourism.Keywords : Branding Promotion, ASEAN Tourism Forum (ATF), Wonderful Indonesia